Trends in Organochlorine Residue Concentrations in Ringed Seal (Phoca hispida) from Holman, Northwest Territories, 1972-91 - Addison, R.F.; Smith, T.G. (ARCTIC, 1998)
Samples of blubber for organochlorine (OC) analysis were collected from ringed seals (Phoca hispida) taken during subsistence hunts at Holman, Northwest Territories, in 1972, 1981, 1989, and 1991. DDT-group residue burdens did not change appreciably between 1972 and 1981, but after 1981 concentrations of p,p'-DDE and p,p'-DDT began to fall. By 1991, p,p'-DDE concentrations were less than half, and p,p'-DDT concentrations about 20%, of their 1972 values. Concentrations of polychlorinated biphenyls (PCB) fell to about one-third of their 1972 values by 1981, and then stayed constant until 1991; small but significant changes in the relative proportions of individual congeners, probably resulting from metabolism, occurred between 1981 and 1991. Concentrations of hexachlorobenzene (HCB) fell by 40 to 50% between 1981 and 1991, but those of alpha and beta hexachlorocyclohexanes (HCH) did not change. Only minor changes were seen in the distribution of other OC pesticides (oxychlordane, cis- and trans-chlordane, cis- and trans-nonachlor, mirex, heptachlor epoxide and dieldrin). Female ringed seals consistently had lower blubber DDT-group and PCB concentrations than males. These temporal trends are consistent with changes in the production and use pattern of some OCs, and with their expected environmental behaviour as inferred from their physico-chemical properties. En 1972, 1981, 1989 et 1991, on a prélevé des échantillons de lard de phoques annelés (Phoca hispida) pris durant des chasses de subsistance à Holman (Territoires du Nord-Ouest), en vue d'en analyser les organochlorés. Les charges des résidus du groupe DDT n'ont pas changé de façon appréciable entre 1972 et 1981, mais après 1981 les concentrations de p,p'-DDE et de p,p'-DDT ont commencé à chuter. En 1991, les concentrations de p,p'-DDE étaient de plus de 50 p. cent inférieures à leurs valeurs de 1972, et celles de p,p'-DDT, d'environ 20 p. cent. En 1981, les concentrations de diphényles polychlorés (PCB) avaient baissé pour atteindre environ un tiers de ...